Guidelines as rationing tools: a qualitative analysis of psychosocial patient selection criteria for cardiac procedures - Giacomini, Mita K. (2001)
BACKGROUND: Cardiac procedure guidelines often include psychosocial criteria for selecting patients that potentially introduce social value judgements into clinical decisions and decisions about the rationing of care. The aim of this study was to investigate the terms and justifications for and the meanings of psychosocial patient characteristics used in cardiac procedure guidelines. METHODS: We selected English-language guidelines published since 1990 and chapters in textbooks published since 1989. These guidelines amalgamated multiple sources of evidence and expertise and made recommendations regarding patient selection for specific procedures. A multidisciplinary team of physicians and social scientists extracted passages regarding psychosocial criteria and developed categories and conceptual relationships to describe and interpret their content. RESULTS: Sixty-five papers met the criteria for inclusion in the study. Forty-five (69%) mentioned psychosocial criteria as procedure indications or contraindications. The latter fell into several categories, including behavioural and psychological issues, relationships with significant others, financial resources, social roles and environmental circumstances. INTERPRETATION: Psychosocial characteristics are portrayed as having 2 roles in patient selection: as risk factors intrinsic to the candidate or as indicators of need for special intervention. Guidelines typically simply list psychosocial contraindications without clarifying their specific nature or providing any justification for their use. Psychosocial considerations can help in the evaluation of patients for cardiac procedures, but they become ethically controversial when used to restrict access. The use of psychosocial indications and contraindications could be improved by more precise descriptions of the psychosocial problem at issue, explanations regarding why the criterion matters and justification of the characteristic using a biological rationale or research evidence.